THE RELATIONSHIP BETWEEN FACTORS THAT CONTRIBUTE TO ANXIETY BEFORE CHILDBIRTH - Siskha Maya Herlina; Yopi Suryatim Pratiwi; Yadul Ulya; Regina Pricilia Yunika (Jurnal Kesehatan Kusuma Husada, 2026)
Background: Anxiety before childbirth is one of the psychological problems often experienced by pregnant women, especially in the final trimester. This condition can be influenced by various factors, both internal and external, that affect a mother’s readiness to face childbirth.Method: This quantitative descriptive design involves 45 samples of pregnant women in their third trimester who are approaching labor. The sampling technique uses purposive sampling to examine whether there’s a relationship between mothers’ age, education, and occupation and anxiety at the community health center in Mataram, West Nusa Tenggara.Result: The research results show that, out of 45 respondents, the P-value from the Pearson chi-square test is 0.018, which is less than 0.05. Therefore, it can be concluded that there is a significant relationship between the factors causing labor and anxiety before labor.Conclusion: There is a significant relationship between factors causing childbirth and anxiety before delivery. Factors causing anxiety before delivery include husband support and parity factors. There is a significant relationship between the factors causing labor and anxiety before giving birth. Factors like the age of the pregnant mother, education, and occupation can affect anxiety in pregnant women in the third trimester before giving birth.